ANALISIS NILAI TAMBAH AGROINDUSTRI MI SEGAR, MI BASAH, BIHUN, DAN SOUN DI PROPINSI LAMPUNG - Aring Hepiana Lestari, Dyah (Lampung University)
The objective of this research is to study the added value of mi segar, mi basah, bihun, and soun agroindustries. Research was conducted in Bandar Lampung and Metro as centres of mi segar, mi basah, bihun, and soun agroindustries in Lampung Province. All of the mi segar, mi basah, bihun, and soun agroindustries in that area were taken as respondents. The result of the study shows that all of mi segar, mi basah, bihun, and soun agroindustries give a positif added value. The largest added value is given by mi basah agroindustry. The margin value of capital and management for mi segar and mi basah agroindustries is larger than the margin value of labour, so that the mi segar and mi basah agroindustries are capital intensive. On the other hand, the margin value of labour for bihun and soun agro industries is larger than the margin value of capital and management, so that the bihun and soun agro industries are labor intensive.